Selection criteria for radiofrequency ablation for colorectal liver metastases in the era of effective systemic therapy: a clinical score based proposal - Stang, Axel (BioMed Central, 2014)
BACKGROUND: At present, there are no widely accepted criteria for the use of radiofrequency ablation (RFA) for the treatment of colorectal liver metastases (CLM) in the context of effective modern-agent therapies. We aimed to define selection criteria for patients with liver-limited CLM who may benefit from adding RFA to systemic therapy with respect to long-term disease control. METHODS: Between 2002 and 2007, 88 consecutive patients received RFA for liver-only CLM during partial remission (PR), stable disease (SD), or progressive disease (PD) after systemic therapy. At a median follow-up of 8.2 years (range 5.2-11.1 years), clinical data were correlated to overall survival (OS) and recurrence-free survival (RFS). RESULTS: Poor OS and RFS correlated significantly with PD to systemic therapy before RFA (HR 5.46; p < 0.0001; and HR 6.46; p < 0.0001), number of ≥4 CLM (HR 3.13; p = 0.0005; and HR 1.77; p = 0.0389), and carcinoembryonic antigen (CEA) level of ≥100 ng/ml (HR 1.67; p = 0.032; and HR 1.67; p = 0.044). The presence of four criteria (PR, ≤3 CLM, ≤3 cm maximum size, and CEA ≤100 ng/ml) selected a subgroup (n = 23) with significantly higher probabilities for OS and RFS at 5 years (39% and 22%,respectively) compared to those without any or up 3 of these criteria (0-27% and 0-9%, p < 0.001, respectively). CONCLUSIONS: A score based on four criteria (response to systemic therapy, ≤3 CLM, ≤3 cm size, low CEA value) may allow to select patients with liver-only CLM for whom additional use of RFA most likely adds benefit in an attempt to achieve long-term disease control. Almost one-fourth of patients fulfilling these four criteria may achieve 5-year survival without disease recurrence following effective systemic plus local RFA treatment.